Faktor yang Memengaruhi Prinsip Konservatisme Akuntansi di Perusahaan yang Terdaftar di Bursa Efek Indonesia - Mardatillah, Alya; Yanthi, Merlyana Dwinda (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Financial reports are guidelines used by various parties in making decisions. However, based on the survey, there are several companies that manipulate financial reports for both personal and company interests.  One of the things that can cause financial reports to not be in accordance with the actual situation is the accounting method used, such as the application of accounting conservatism. This research was conducted to test the influence of the independent variables consisting of profitability, leverage, financial distress,  and managerial ownership on the dependent variable, namely accounting conservatism. The population of this research consists of 305 data from financial sector companies listed on the Indonesia Stock Exchange from 2020 to 2022. Using purposive sampling techniques, only 87 data meet the research sample criteria and will be analyzed in this research. The research uses a multiple linear regression analysis method which aims to test the influence of more than one independent variable on one dependent variable. The results of this research are that profitability, leverage, financial distress, and managerial ownership simultanously influence accounting conservatism. Profitability, financial distress and leverage partially have no effect on accounting conservatism. Meanwhile, managerial ownership partially influences accounting conservatism.